Nursing Care of Patients with Autism - Hussain Yassin Hussain Alalowy; Alhuwayji, Haifa Ahmed; Abdullah Essa Ali Almani; Maryam Nasser Abduallah Albrahim; Althani, Ruqayyah Matuq; Hawra Abdullah Ali Aldrees; Hibah Saleh Farhan Alfarhan; Abdullah Ali Abdullah Alqurayn; Aldrees, Eman Abdullah; Alsalamin, Ruqayah Jawad; Alibrahim , Thikra Ibrahim; Ali Hussain A Alshaghab; et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Autism Spectrum Disorder (ASD) presents unique challenges in healthcare due to its diverse manifestations and the specific needs of affected individuals. Nursing care for patients with autism requires specialized approaches to effectively address communication, behavioral, and sensory issues. This review highlights the key aspects of nursing care for patients with autism, including assessment strategies, communication techniques, and individualized care plans. The aim is to provide a comprehensive guide to improve healthcare outcomes and quality of life for individuals with autism. Keywords: Nursing Care, Autism, Autism spectrum disorder. Received Date: April 18, 2024 Accepted Date: May 16, 2024 Published Date: June 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/167 DOI: https://doi.org/10.5281/zenodo.12802919